Determination of Total Nitrosamines in Vegetables Cultivated Organic and Conventional Using Diamond Electrode - Coffacci, Lidiane [UNESP]; Codognoto, Lucia; Fleuri, Luciana F. [UNESP]; Lima, Giuseppina P.P. [UNESP]; Pedrosa, Valber A. [UNESP] (Springer Nature, 2013)
Vegetables were analyzed for total N-nitrosamines (NAs) and the influence of disinfection processes was assessed. Differences in NAs found in cabbage, spinach, and broccoli were determined by square wave voltammetry using a boron-doped diamond electrode. Analysis of samples showed that all samples contained detectable levels of NAs but the results indicated that organic contained less than conventionally grown products. The sum of the total NAs was higher in the cabbage samples, ranging between 2.8-3.1 ppb and lower in broccoli samples at 0.2-1.1 ppb. The method described is simple, rapid, selective, and sensitive. The results suggested that the disinfection process affects the level of NAs, in this manner affecting the level of human exposure to NAs. © 2012 Springer Science+Business Media New York.
Keywords: Electrochemistry; Nitroso compounds; Organic food; Boron-doped diamond electrodes; Diamond electrode; Disinfection process; Human exposures; N-nitrosamines; Organic foods; Square wave voltammetry; Disinfection; Voltammetry; Vegetables